O riso como expressão de um posicionamento na cidade: o encontro de Demócrito e Hipócrates (Nuntius Antiquus, 2009)
The Pseudo-Hippocratic Letters relate the fictitious meeting between Democritus and Hippocrates. This document is the basis which allows us to think about how the hippocratic tradition and Democritus’ philosophy treat the concepts of man’s and city’s health. This paper aims to show some aspects of the relationship between man and the city, given the concept of health present in the Pseudo-Hippocratic Letters and also in both traditions which inspire them.